A haloarchaeal ferredoxin electron donor that plays an essential role in nitrate assimilation. (21st November 2011) - Zafrilla, Basilio; Martínez-Espinosa, Rosa María; Bonete, María José; Butt, Julea N.; Richardson, David J.; Gates, Andrew J.
Abstract : In the absence of ammonium, many organisms, including the halophilic archaeon Haloferax volcanii DS2 (DM3757), may assimilate inorganic nitrogen from nitrate or nitrite, using a ferredoxin-dependent assimilatory NO3 − /NO2 − reductase pathway. The small acidic ferredoxin Hv -Fd plays an essential role in the electron transfer cascade required for assimilatory nitrate and nitrite reduction by the cytoplasmic NarB- and NirA-type reductases respectively. UV–visible absorbance and EPR spectroscopic characterization of purified Hv -Fd demonstrate that this protein binds a single [2Fe–2S] cluster, and potentiometric titration reveals that the cluster shares similar redox properties with those present in plant-type ferredoxins.